2009
DOI: 10.3917/spub.093.0263
|View full text |Cite
|
Sign up to set email alerts
|

Les épidémies de choléra au Mali de 1995 à 2004

Abstract: Cholera epidemics have been constant in Mali since the beginning of the 21st century in spite of the efforts which have been made to prevent and control them. A rigorous analysis of the factors which support this persistence and appropriate measures are essential to reverse cholera in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Legba et al [20] in Benin reported the same situation. Jaureguiberry et al [21] and Dao et al [2] also observed this phenomenon in Madagascar and Mali respectively. These Cholera control in African countries is mainly focused on disease surveillance and epidemic response according to Makoutodé et al [3], Ndour et al [12].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Legba et al [20] in Benin reported the same situation. Jaureguiberry et al [21] and Dao et al [2] also observed this phenomenon in Madagascar and Mali respectively. These Cholera control in African countries is mainly focused on disease surveillance and epidemic response according to Makoutodé et al [3], Ndour et al [12].…”
Section: Discussionmentioning
confidence: 76%
“…Africa is the most affected continent: reported cases represent between 95% and 99% of the world total each year [1]. This disease is due to uncleanliness and poor hygiene conditions occurring in communities with low living standards [2]. Surveillance and response are part of the strategy to control diseases with epidemic potential, including cholera proposed by WHO to affected countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dans 99% des cas chez l'homme, la transmission se fait par le contact avec les chiens domestiques lors d'une morsure, griffure ou léchage (3). (10). La prévalence de la vaccination chez les chiens de notre étude était très faible, seulement de 4,41%.…”
Section: Introductionunclassified